Entrepreneurial Marketing and SME Performance: The Mediating Role of Process and Product Innovation in Bangladesh - Nishu, Md Ahsanuzzaman; Tat, Huam Hon; Kumarusamy, Risidaxshinni; Hafiz, Nusrat; Karim, Iftekhar Ul; Fazal, Syed Ali; Hasnat, Md. Abu (Journal of Posthumanism, 2025)
SMEs in Bangladesh are facing limited access to finance and a lack of innovative, entrepreneurial, and marketing skills. They have underdeveloped marketing and sales channels due to financial constraints. Entrepreneurial Marketing (EM), positioned at the intersection of entrepreneurship and marketing, offers a promising solution to these resource-constrained SMEs. While successful EM practices have been documented primarily in developed country contexts, there remains a significant gap in understanding its impact on SMEs in emerging economies like Bangladesh. Furthermore, the role of multiple innovation capabilities in mediating EM’s effects on SME performance has yet to be explored in this context. This research addresses these gaps by investigating the synergistic effects of EM’s seven-dimensional framework on the performance of Bangladeshi SMEs, with process and product innovation serving as mediators. The conceptual framework of the study, supported by the Dynamic Capabilities Theory, was analysed using data collected from a quantitative survey of 355 SME owners or managers selected with the convenience sampling technique. PLS-SEM analysis reveal that EM positively influences process and product innovation. Consequently, process and product innovation significantly enhance SME performance. Additionally, the study highlights the critical mediating roles of these innovation categories in the relationship between EM and SME performance.